Beyond Conventional Business Planning : Building and online startup in quick-paced economy - Šimek, Vojtěch (2016)
First part of the thesis compares available approaches on business planning, namely the traditional and newly emerged and proposes a Business Planning Approach Selection Framework that should help (newbie) entrepreneurs with orientation in the chaotic business planning world and choosing an approach suiting their specific needs. Conclusion of the theoretical part is that both the traditional and modern business plans have their role in todays business environment. While the old are great for external presentation and funds securing, the new enable to create more complex process for planning successful business from the original idea to and beyond their launch, building on customer feedback and gradual iterations. The practical part then builds on the theoretical research and aims to check feasibility of an actual business project, a multisided platform mediating sales of automotive financial products. It describes the model refinement and product creation process as well as eventually proves viability and feasibility of the whole business.